2022
DOI: 10.3390/vaccines10060848
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Vaccination against SARS-CoV-2 during Pregnancy in Favor of the Mother/Newborn Dyad

Abstract: When the first vaccines against SARS-CoV-2 emerged, pregnant women were excluded from clinical trials, so vaccine recommendations were initially adjourned, with late initiation for this populational category. The present study aims to quantify the serum and breastmilk values of SARS-CoV-2 spike protein antibodies in both the mother and her newborn after complete vaccination during pregnancy. Ninety-one vaccinated patients were included, some of whom presented COVID-19 infection during pregnancy. In the deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…They concluded that “receiving both vaccine doses before delivery and longer latency from vaccination to delivery was associated with a higher IgG concentration in infants and stronger immunity” [ 52 ]. This result was also confirmed in other studies [ 86 , 87 ]. Prabhu et al studied 122 pregnant women, of whom 55 and 67 had received their first and second mRNA vaccine doses, respectively, before delivery.…”
Section: Covid-19 Vaccination and Transplacental Transfer Of Antibodiessupporting
confidence: 92%
“…They concluded that “receiving both vaccine doses before delivery and longer latency from vaccination to delivery was associated with a higher IgG concentration in infants and stronger immunity” [ 52 ]. This result was also confirmed in other studies [ 86 , 87 ]. Prabhu et al studied 122 pregnant women, of whom 55 and 67 had received their first and second mRNA vaccine doses, respectively, before delivery.…”
Section: Covid-19 Vaccination and Transplacental Transfer Of Antibodiessupporting
confidence: 92%
“…Publications concerning the placental transfer of vaccine-induced antibodies are very limited, and all are studies on mRNA vaccine on singleton pregnancies [ 7 , 10 , 12 , 13 ]. To the best of our knowledge, this is the first report concerning the placental transfer of passive immunization of COVID-19 from the mother to the twin fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data on the interval of schedules to maximize the passive immunity in newborns and type of vaccines are currently very limited. Only a few studies have been published, including BNT-162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna) vaccines [ 12 , 13 , 16 ] and a case report of inactivated virus antigen (CoronaVac ® ) [ 17 ]. The antibody levels were much higher in mothers who had received two doses of an mRNA vaccine than those who received only one dose [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the limited literature, three studies reported that anti-SARS-CoV-2 antibodies were not detected in infant sera of mothers vaccinated while lactating (sample sizes = 8, 5, and 21) (31, 34, 35), and one study reported that anti-SARS-CoV-2 IgG was detected in the sera of 23% (3 of 13) of breastfed infants of mothers vaccinated after delivery (36). In contrast, it is clear that transplacental transmission after maternal vaccination or infection results in detectable levels of anti-SARS-CoV-2 antibodies in infant sera (34,(37)(38)(39)(40). It is important to keep in mind that COVID-19 could manifest as an asymptomatic infection, both among infants and among lactating women.…”
Section: Discussionmentioning
confidence: 99%